GENETIC SOURCES FOR BREEDING BUSHY AND SHORT-VINE WATERMELON CULTIVARS - G. A. Tekhanovich; A. G. Elatskova; Yu. A. Elatskova (Труды по прикладной ботанике, генетике и селекции, 2019)
Background. When studying the collection of watermelon, it is important to disclose its genetic potential by identifying spontaneous mutations, using its accessions in crosses, and analyzing inheritance of its main traits in hybrids. One of the priorities in watermelon breeding is to develop and produce genetic sources of bushy and short-vine forms with stable manifestation of their morpho-biological characters under various environmental conditions.Material and methods. Accessions from the watermelon collection (local landraces, commercialized and promising cultivars, hybrids and lines obtained in the process of work) of diverse ecogeographic groups served as the material for this research. Description of morphological characters and assessment of economically useful ones were based on the guidelines for studying and maintaining the cucurbit collection and the guidelines for cucurbit crop breeding, both developed by VIR.Results. Variability and inheritance of the bushiness and short vine characters were studied in watermelon accessions according to the features of their growth and development. The habitus of the bushy forms is shaped by the length of stems (0.8– 1.2 m) and very short (2–3 cm) internodes. Short-vine plant stems are 1.3–1.5 m long. Short-vine plants in the early period of development distinctly stand out for their compact bush, if compared with long-vine forms. Short vines are developed due to short internodes (4–5 cm) and a smaller number of lateral shoots.Conclusion. Many years of studying the watermelon collection in the field resulted in identification of promising genetic sources for the breeding of bushy and short-vine cultivars: bushy dissected-leaf lines (KRL) – KRL 694, KRL 656, KRL 376 and KRL 394; bushy entire-leaf lines (KTsL) – KTsL 760/13; yellow-green bushy dissectedleaf lines (ZhZKRL) – ZhZKRL; short-vine watermelon lines (KPL) – KPL 774 and KPL 368. The developed lines differ in morpho-biological and economically useful characters (yield,fruit quality, growing season duration, etc.). They possess resistance to diseases (fusarium wilt and anthracnose) and environmental stressors. The lines are offered for use in the breeding of new bushy and short-vine cultivars and improvement of the existing ones, with various combinations of morpho-biological and economic traits. Brief descriptions of main economically valuable characters of the breeding lines are presented.